The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1590/s2179-975x5117
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of periphytic Zygnematophyceae (Streptophyta) in urban eutrophic ponds from central Brazil (Goiânia, GO)

Abstract: Aim This study aimed to investigate the community structure of Zygnematophyceae algae in the periphyton of nine shallow urban eutrophic ponds from central Brazil. Additionally, we compared two different substrates, hypothesizing that community structure attributes (chlorophyll a; Zygnematophyceae density, composition and richness) would differ between them. Methods Samples were carried out in August 2014. Periphyton was collected from two different substrates, macrophyte (epiphyton) and rocks (epilithon). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…where: [TP] is the total P concentration of the lake water in mg L −1 , LP is the P loading rate, TR is the calculated retention, and Z is the average reservoir depth [31,33]. The model proposed by Lamparelli [33,35] for tropical reservoirs was developed from the classic model of Carlson (1977) and established new relationships to determine the TSI, generating the model that uses concentrations (µg L −1 ) of: total phosphorus (TP) (Equation ( 2)) and chlorophyll a (Chl-a) (Equation ( 3)), and calculating the value of the TSI (Equation ( 4)) from the average of the indexes obtained through Equations ( 2) and (3).…”
Section: Trophic Status Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…where: [TP] is the total P concentration of the lake water in mg L −1 , LP is the P loading rate, TR is the calculated retention, and Z is the average reservoir depth [31,33]. The model proposed by Lamparelli [33,35] for tropical reservoirs was developed from the classic model of Carlson (1977) and established new relationships to determine the TSI, generating the model that uses concentrations (µg L −1 ) of: total phosphorus (TP) (Equation ( 2)) and chlorophyll a (Chl-a) (Equation ( 3)), and calculating the value of the TSI (Equation ( 4)) from the average of the indexes obtained through Equations ( 2) and (3).…”
Section: Trophic Status Assessmentmentioning
confidence: 99%
“…Water quality and productivity of lakes and reservoirs are largely controlled by the quantity and quality of external nutrient loads [1]. An excess of nutrients, in turn, can greatly intensify the natural eutrophication process, currently considered as one of the main problems affecting water quality [2,3]. Furthermore, climate warming will tilt the CH 4 balance towards higher lake emission with this impact exacerbated by the eutrophication of the lakes [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more recent floristic investigations demonstrate that many desmids known as indicators of oligotrophic conditions have been commonly found in meso‐eutrophic to eutrophic waters, while eutrophic taxa have been frequently recorded in effluents from agricultural complexes (Fehér 2003, Stamenković and Cvijan 2008, Ferragut and Bicudo 2009, 2012, de Silva et al. 2018). In general, this indicated that desmids shifted their optima to high concentrations of nutrients and various pollutants, thus, some of them could possibly be used as absorbents of excess nutrients in wastewaters.…”
mentioning
confidence: 99%